Sex differences in measures of central sensitization and pain sensitivity to experimental sleep disruption: implications for sex differences in chronic pain. Issue 2 (29th October 2018) - Smith, Michael T; Remeniuk, Bethany; Finan, Patrick H; Speed, Traci J; Tompkins, D Andrew; Robinson, Mercedes; Gonzalez, Kaylin; Bjurstrom, Martin F; Irwin, Michael R
Abstract: Study Objectives: Females demonstrate heightened central sensitization (CS), a risk factor for chronic pain characterized by enhanced responsivity of central nervous system nociceptors to normal or subthreshold input. Sleep disruption increases pain sensitivity, but sex has rarely been evaluated as a moderator and few experiments have measured CS. We evaluated whether two nights of sleep disruption alter CS measures of secondary hyperalgesia and mechanical temporal summation in a sex-dependent manner. We also evaluated differences in measures of pain sensitivity. Methods: Seventy-nine healthy adults (female n = 46) participated in a randomized crossover experiment comparing two consecutive nights of eight pseudorandomly distributed forced awakenings (FA [−200 min sleep time]) against two nights of undisturbed sleep (US). We conducted sensory testing the mornings following Night 2; the heat-capsaicin pain model was used to induce secondary hyperalgesia. Results: FA reduced total sleep time (REM and NREM Stage 3) more profoundly in males. We observed divergent, sex-dependent effects of FA on secondary hyperalgesia and temporal summation. FA significantly increased secondary hyperalgesia in males and significantly increased temporal summation in females. Sex differences were not attributable to differential sleep loss in males. FA also significantly reduced heat-pain threshold and cold pressor pain tolerance, independently of sex. Conclusions: Sleep disruption enhances different pain facilitatory measures of CS in males and females suggesting that sleep disturbance may increase risk for chronic pain in males and females via distinct pathways. Findings have implications for understanding sex differences in chronic pain and investigating sleep in chronic pain prevention efforts.